PENGEMBANGAN MOBILE LEARNING PENGUKURAN LISTRIK UNTUK SISWA PROGRAMKEAHLIAN TITL DI SMK - Tafrikhatin, Asni (Politeknik Dharma Patria Kebumen, 2018)
This study aims to developing mobile learning material electrical measurement. The research is a research and development that uses Waterfal research modell. Waterfall model development which consists of four stages: communication, planning, modelling, and construction. The subjects of this study were teachers and students of X class of Electrical Installation Study Program from SMK Negeri 3 Yogyakarta, SMK Negeri 1 Pundong, SMK Taman Siswa Yogyakarta, and SMK Muhammadiyah 3 Yogyakarta. The data were analyzed using descriptive. The result of mobile learning feasibility assessment according to validator was 80.30 and students equal to 85.59 from scale 100 so categorized as